Phaeophyceaean (Brown Algal) Extracts Activate Plant Defense Systems in Arabidopsis thaliana Challenged With Phytophthora cinnamomi - Islam, Md Tohidul; Gan, Han Ming; Ziemann, Mark; Hussain, Hashmath Inayath; Arioli, Tony; Cahill, David (Frontiers in Plant Science, 2020)
Seaweed extracts are important sources of plant biostimulants that boost agricultural productivity to meet current world demand. The ability of seaweed extracts based on either of the Phaeophyceaean species Ascophyllum nodosum or Durvillaea potatorum to enhance plant growth or suppress plant disease have recently been shown. However, very limited information is available on the mechanisms of suppression of plant disease by such extracts. In addition, there is no information on the ability of a combination of extracts from A. nodosum and D. potatorum to suppress a plant pathogen or to induce plant defence. The present study has explored the transcriptome, using RNA-seq, of Arabidopsis thaliana following treatment with extracts from the two species, or a mixture of both, prior to inoculation with the root pathogen Phytophthora cinnamomi. Following inoculation, five time points (0 - 24 h post-inoculation) that represented early stages in the interaction of the pathogen with its host were assessed for each treatment and compared with their respective water controls. Wide scale transcriptome reprogramming occurred predominantly related to phytohormone biosynthesis and signaling, changes in metabolic processes and cell wall biosynthesis, there was a broad induction of proteolysis pathways, a respiratory burst and numerous defence-related responses were induced. The induction by each seaweed extracts of defence-related genes coincident with the time of inoculation showed that the plants were primed for defence prior to infection. Each seaweed extract acted differently in inducing plant defence-related genes. However, major systemic acquired resistance (SAR)-related genes as well as salicylic acid-regulated marker genes (PR1, PR5 and NPR1) and auxin associated genes were found to be up-regulated commonly compared with the controls following treatment with each seaweed extract. Moreover, each seaweed extract suppressed P. cinnamomi growth within the roots of inoculated A. thaliana by the early induction of defence pathways and likely through ROS-based signaling pathways that were linked to production of ROS. Collectively, the RNA-seq transcriptome analysis revealed the induction by seaweed extracts of suites of genes that are associated with direct or indirect plant defence in addition to responses that require cellular energy to maintain plant growth during biotic stress.